Clinical evaluation of twenty cases of heterotopic gastric mucosa of upper esophagus during five-year observation, using gastroscopy in combination with histopathological and microbiological analysis of biopsies - Latos, Wojciech; Sieroń-Stołtny, Karolina; Kawczyk-Krupka, Aleksandra; Operchalski, Tomasz; Cieślar, Grzegorz; Kwiatek, Sebastian; M. Bugaj, Andrzej; Sieroń, Aleksander (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: Heterotopic gastric mucosa of the upper esophagus (HGMUE) may be connected with disorders of the upper gastrointestinal tract, exacerbated by Helicobacter pylori. Furthermore, HGMUE may be the origin of malignant progression to cervical esophageal carcinoma. Material and methods : In this work, 20 patients with diagnosed heterotopic gastric mucosa of the upper esophagus (HGMUE) were subjected to 5-year follow-up to determine the extent and structure of histopathological changes within HGMUEs, as well as HGMUE dysplasia and metaplasia, and risk of their malignant transformation. As a diagnostic tool to describe localization, form, size and surface feature of HGMUEs, endoscopy was used. At the same time, the biopsies were collected for histopathological and microbiological analysis. Results: In examined patients, HGMUEs were associated with inflammation, chronic gastritis, hiatus hernia, duodenal bulb erosion and ulcer and infection of H. pylori. Intestinal metaplasia and low grade dysplasia were also indicated. During 5 years of observation, both the clinical and histopathological image of diagnosed HGMUEs was stable. The patients with detected presence of H. pylori were treated with triple or quadruple therapy. These results show that HGMUEs may be associated with severe complications in the gastrointestinal tract, such as infection by H. pylori, hiatus hernia or duodenal ulcer. Although dysplasias and metaplasias found in diagnosed HGMUEs were not very numerous and relatively stable both clinically and histopathologically, at the present stage of the study we cannot exclude the possibility of HGMUE malignant transformation.